The Benefit of Enterprise Risk Management (ERM) On Firm Performance - Mochamad Muslih (Universitas Trisakti, 2018)
There were inconsistencies on the results of some ERM researches formerly. There were some variabilities on the benefits and obstacles hampering the implementation of ERM. The purpose of this research is to study the benefits of Enterprise Risk Management (ERM) to increase firm performance.This research used quantitative method, using the statistical software of eviews 9 to process the data samples. The Sampled firms arecompanies listed in the Indonesian stock exchange. 108 questionnaires were filled by the respondents. The variables measured are firm performances and enterprise risk management. The implementation of corporate governance and firm performance are also measured as control variables. Regression procedures were used to analyze the data samples. Some secondary data were also used to enrich analizing the research phenomena.The research findings showed a significant relationship between ERM with firm performance. The effect of ERM as independent variable on firm performance waso significant so that the influence of corporate governance (CG) as control variable became insignificant. Actually based on individual regression, CG influence on firm performance is significant. But totally the influence became insignificant, hampered by the magnitude of ERM influence significancy. These findings add to positive heuristics of falsification model of research as proposed by Imre Lakatos.